Advancements in Throughput, Lifetime, Purification, and Workflow for Integrated Nanoscale Deterministic Lateral Displacement. Issue 4 (4th March 2021) - Wunsch, Benjamin H.; Hsieh, Kuan Yu; Kim, Sung‐Cheol; Pereira, Michael; Lukashov, Stanislav; Scerbo, Chris; Papalia, John M.; Duch, Elizabeth A.; Stolovitzky, Gustavo; Gifford, Stacey M.; Smith, Joshua T.
Abstract: Nanoscale deterministic lateral displacement (nanoDLD) has emerged as an effective method for separating nanoscopic colloids for applications in molecular biology, yet present limits in throughput, purification, on‐chip filtration, and workflow restricting its adoption as a practical separation technology. To overcome these impediments, array scaling and parallelization for integrated nanoDLD ( i ‐nanoDLD) enrichment devices are developed to achieve a density of ≈83 arrays mm −2 with 31 160 parallel arrays, producing an ≈30‐fold concentration of the target colloid and a record throughput of 17 mL h −1 . Purification using a dual‐fluid input embodiment of i ‐nanoDLD is demonstrated to successfully remove background contaminants from target colloid samples, including urine. Used serially, high‐throughput enrichment and purification chips achieve >1700 gain in particle over protein concentration compared to input sample. Additionally, integration of upstream filter banks shows improved operation lifetime > 7× for particles with diameters close to the gap size. Finally, the integrated design and associated flow rates allow a straightforward approach to chip‐to‐world interfacing as demonstrated using a prototype system for facile, turn‐key sample processing. Collectively, these developments advance nanoDLD into the range of sample volumes and process times needed for research and clinical samples. Abstract : Integrated, parallelized nanoscale deterministic lateral displacement arrays using silicon nanolithography are developed to address key challenges of sample preparation. Geometric scaling of array density enables milliliter processing volumes, on‐chip filtration, and synchronized focused injection for isolation of colloids from background contaminates. Short processing times with high flow rates allow combining devices to produce a full purification technique for nanoscale colloids.